Pengaruh Mortalitas Larva Aedes aegypti Dan Larva Culex sp Yang Di Aplikasikan Dengan Ekstrak Air Pronojiwo (Euchresta horsfieldii) - P.D.S. Febriyani; Diah Karunia Binawati (FMIPA : Universitas PGRI Adi Buana, 2015)
The aims of this study to test the killing effect of aqueous extract of leaves Pronojiwo (Euchresta horsfieldii) on mortality Aedes aegypti larvae and larvae of Culex sp. Study was conducted in a completely randomized exprimental design with 5 level of water extract of E. horsfieldii (0,1%,10%,20%,30% and 40%), each of treatment was 5 replication. Application is done by spraying water extract of leaves Pronojiwo to 2 types of larvae. For each treatment contains 20 larvae. Observations the larval mortality 24 hours after application of aqueous extracts of leaves Pronojiwo. The results showed that the water extract of leaves Pronojiwo significant effect (P <0.05) on mortality of larvae of Aedes aegypti and Culex sp. The results showed that the water extract of leaves Pronojiwo can effectively turn off the larvae of Aedes aegypti at a concentration of 40%, while the larvae of the mosquito Culex sp can be deadly effective at a concentration of 20%. Keywords: Leaves Pronojiwo mortality, larvae of Aedes aegypti Culex sp